2007
DOI: 10.1007/s12015-007-0001-y
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt Signal Transduction Pathway in Stem Cells and Cancer Cells: Influence on Cellular Invasion

Abstract: The regulative network conducting adult stem cells in endogenous tissue repair is of prime interest for understanding organ regeneration as well as preventing degenerative and malignant diseases. One major signal transduction pathway which is involved in the control of these (patho)physiological processes is the Wnt pathway. Recent results obtained in our laboratories showed for the first time that canonical Wnt signaling is critically involved in the control of the migration/invasion behaviour of human mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 113 publications
2
87
0
2
Order By: Relevance
“…This is supported by the observation that PTNtreated fAEC II had fibroblast-like F-actin distribution on the edge of the wound area. Furthermore, a canonical Wnt signaling pathway is important for the cancer cell invasion and migration (32). Our results showed that PTN activated the Wnt/␤-catenin signaling.…”
Section: Discussionmentioning
confidence: 59%
“…This is supported by the observation that PTNtreated fAEC II had fibroblast-like F-actin distribution on the edge of the wound area. Furthermore, a canonical Wnt signaling pathway is important for the cancer cell invasion and migration (32). Our results showed that PTN activated the Wnt/␤-catenin signaling.…”
Section: Discussionmentioning
confidence: 59%
“…Ubiquitously expressed PTK7 pseudo-kinase is an essential component of the non-canonical Wnt/PCP signaling pathway, arguably one of the most important cellular pathways in eukaryotes (46,47). At its most basic level, polarity may be considered as the generation of asymmetry within a single cell, whether the result of the asymmetry is a directed movement that leads to cellular migration or to the relocalization of specific multicellular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Wnt target gene will contribute to the development of cancer in terms of proliferation, invasion and metastasis, and angiogenesis (Taketo, 2006;Neth et al, 2007). Additionally, inhibition of Wnt signalling could reduce cell proliferation and increase apoptosis in pancreatic adenocarcinoma cells (Miao et al, 2003;Pasca di Magliano et al, 2007;Nawroth et al, 2007).…”
Section: Discussionmentioning
confidence: 99%